Thin and superthin free flaps: An innovative approach to pediatric extremity reconstruction. Issue 11 (November 2022) - Glass, Graeme E.; Staruch, Robert MT; Sivakumar, Branavan; Stotland, Mitchell A.
Abstract: Introduction: Published standards for the management of open extremity fractures have improved limb salvage, fracture union, and deep infection rates, but the aesthetic and functional importance of our flap choices has been overlooked. Thin and superthin free flaps exhibit advantages over traditional free flaps in some situations but have seldom been reported in children. The aim of this paper is to present our experience of thin and superthin free flaps in pediatric extremity reconstruction. Methods: Children (≤13 years) who underwent soft tissue reconstruction using a thin and superthin free flap following major extremity trauma are presented. Results: Five patients (5 flaps) met the inclusion criteria. The median age was 9 (range 6–13). There were 3 Gustilo IIIB open fractures and 2 multiplanar degloving injuries. The median mangled extremity severity score (MESS) was 4 (range 2–6). The median time from injury to definitive soft tissue closure was 72 h (range 28–120 h). Four anterolateral thigh (ALT) flaps were raised as thin flaps, and 1 superficial circumflex iliac artery perforator (SCIP) was raised as a superthin flap. There was one re-exploration owing to venous congestion, and a second venous anastomosis was performed to enhance flap drainage. The same ALT flap exhibited necrosis at one margin, which was debrided and grafted before discharge. There were no other flap complications. No flap-related secondary surgeries were required. Conclusion: Thin and superthin free flaps are viable options in pediatric extremity reconstruction. They exhibit excellent aesthetic and functional contouring when a slender fasciocutaneous flap is needed, especially when body habitus renders traditional options unfavorable.